Studi Literatur Self-Regulated Learning Dalam Pembelajaran Matematika di Sekolah Dasar - Muhammad Hash Hashol Haq; Ellianawati Ellianawati; Bambang Subali; Ani Rusilowati (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
Low mathematics learning outcomes in elementary schools highlight the need for a systematic review of self-regulated learning (SRL) as a strategy to improve learning quality. This study aims to synthesize empirical studies on SRL in elementary school mathematics through a Systematic Literature Review (SLR) guided by PRISMA 2020. A total of 37 articles published between 2021 and 2026 were identified and analyzed using the MMAT 2018 quality appraisal tool. Findings reveal that quasi-experimental designs dominate research in this field, with Zimmerman's SRL cycle model as the most frequently referenced theoretical framework. Five groups of SRL-based interventions were identified, namely cooperative learning models, adaptive digital technology, explicit teacher instruction, metacognitive and feedback approaches, and contextual learning materials, all of which demonstrated positive impacts on student learning outcomes and mathematical abilities. The success of SRL implementation is determined by teacher instruction quality, technological support, and social engagement, while the main barriers include limited teacher competence and curriculum density. This study recommends the systematic integration of SRL into the regular curriculum and the development of standardized SRL measurement instruments for the elementary school context.